Fatores associados a infecção pelo HIV em pessoas privadas de liberdade: um estudo de caso-controle - Gois, Joelma Goetz de (2021)
Persons deprived of their liberty represent one of the groups identified as key populations, among whom there is a greater risk of HIV infection. When compared to the general population, those deprived of liberty have an average of five times more chances of being infected with HIV, this is due to conditions in the prison environment itself, associated with behavioral factors characteristic of this population. Therefore, the objective of the present study was to identify factors associated with HIV infection in the deprived of liberty population of the state of Paraná. To this end, a case-control study was outlined corresponding to a sub-project based on a hat project entitled “Prevalence of HIV and hepatitis B and C in the prison population of the state of Paraná”. The total sample corresponded to 54 male deprived of liberty, of these, 18 cases reactive to HIV and 36 non-reactive. For data analysis, the Mann-Whitney U test was used to compare numerical variables and binary logistic regression to identify risk and protective factors for HIV infection. Significance was set at p <0.05 and 95% confidence interval (CI). The median age corresponded to 30 years for both groups, with no significant differences (p> 0.05). In the analysis of the main variables included in the logistic regression model, the presence or history of STI (OR = 11.506 [95% CI = 2.031 - 65.181], p = 0.006) was a risk factor for HIV. On the other hand, factors such as not having an HIV test (OR = 0.148 [95% CI = 0.024 - 0.911], p = 0.039) and receiving an intimate visit (OR = 0.052 [95% CI = 0.005 - 0.576], p = 0.016) were less likely to be at risk for HIV. The results suggest the need to expand STD information and prevention actions in the prison environment, as well as the importance of further studies on intimate visits in prisons, which presented itself as a protective factor against HIV in the present study. Finally, the aim is to monitor HIV continuously through periodic testing, thus seeking to reduce the damage and incidence of HIV infection in the deprived of liberty population of the state of Paraná.